A long run analysis of the price dynamics in Guadeloupe : theoretical and empirical consideration - Borda, Patrice ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2001)
Seeks to determine the role of french inflation in explaining the regional price dynamic. Focuses on Guadeloupe economy